Physicochemical Characteristics, Nutrient Content, Proximate Composition and Antioxidant activities of edible red seaweeds (Kappaphycus alvarezii, Eucheuma spinosum and Eucheuma striatum) from Sabah, Malaysia - Farah Nurshahida, M. S.; Nurul Aini, Mohd Azman; Nazikussabah, Zaharudin; Wan Mohd Faizal, Wan Mahmood; Aida Hamimi, Ibrahim (Universiti Malaysia Pahang, 2019)
Kappaphycus alverazii (KA), Eucheuma spinosum (ESp) and Eucheuma striatum (ESt) are widely farmed in Kunak, Sabah for food and carrageenan sources. This study was evaluated the nutritional and mineral compositions, physiochemical properties and antioxidant activities of those edible KA, ESp and ESt seaweeds. Results of physicochemical properties and nutritional profile reveal the range of dietary fibre (12.5-8.10% DW), carbohydrate (71.83-70.28% DW), crude protein (3.73-1.56% DW) and lipid content (0.05-0.02% DW) of the three red seaweeds species. KA, ESp and ESt contains biologically important amino acids including Arginine, Threonine, Tyrosine, Valine with total range 15-20 mg/g DW. 7 compositions of mineral evaluated are varies according to the species, with Esp showed the highest mineral contents of Ca (202.65 mg/100g DW), Mg (299.48 mg/100g DW) and KA exhibited highest Fe content with 50.49 mg/100g DW (p<0.05). Physiochemical properties value of swelling capacity (SC) and oil retention capacity (ORC) in KA species showed the highest (p<0.05) compare to ESp and ESt and water retention capacity (WRC) in ESp species was significant difference than KA and ESt (p<0.05).The antioxidant activities (DPPH assay) and total phenolic content (TPC) of three seaweeds species indicated KA displayed highest TPC (19.17 + 0.04 mg GAE/g DW) and the lowest radical scavenging activity in DPPH assay (31.24% DPPH inhibition). The research highlighted is to support the local agricultural commodity in Sabah by creating the nutritional data especially for Eucheuma species and comparing nutritional value with other species and vegetable. The findings also suggest that KA, ESp and ESt. exhibit potent nutritional value could be used as a source of nutrients for human and animals.